The stress-buffering role of friendships in young people with childhood threat experiences: a preliminary report - König, Maximilian; Berhe, Oksana; Ioannidis, Konstantinos; Orellana, Sofia; Davidson, Eugenia; Kaser, Muzaffer; Moreno-López, Laura; van Harmelen, Anne-Laura (European journal of psychotraumatology, 2023)
Background: High-quality friendships have a positive impact on the mental health of young people with childhood adversity (CA). Social stress buffering, the phenomenon of a social partner attenuating acute stress responses, is a potential yet unexplored mechanism that may underlie this relationship. Objective: This study examined whether perceived friendship quality was related to better mental health and lower neural stress response in young people with CA. Method: A total of N = 102 young people (aged 16-26) with low to moderate CA were included in the study. We first investigated associations between friendship quality, mental health, and CA. In a representative subset (n = 62), we assessed neural stress responses using the Montreal Imaging Stress Task. In our sample, CA was best described along two dimensions resembling threat or deprivation like experiences. Hence, we investigated both cumulative and dimensional effects of CA. Results: We found no support for social thinning after CA, meaning that the severity of CA (cumulative or dimensional) did not differentially impact friendship quality. High-quality friendships, on the other hand, were strongly associated with better mental health. Furthermore, acute stress increased state anxiety and enhanced neural activity in five frontolimbic brain regions, including the left hippocampus. We found weak support that threat experiences interacted with friendship quality to predict left hippocampal reactivity to stress. However, this effect did not survive multiple comparison correction. Conclusion: The absence of social thinning in our sample may suggest that the risk of developing impoverished social networks is low for rather well-functioning young people with low to moderate CA. Regardless, our findings align with prior research, consistently showing a strong association between high-quality friendships and better mental health in young people with CA. Future research is needed to examine whether friendships aid neural stress responses in young people with childhood threat experiences. Young people with childhood adversity underwent acute stress induction, eliciting frontolimbic reactivity.High-quality friendships were strongly associated with better mental health.Weak support for friendship stress buffering did not survive multiple comparison correction. Young people with childhood adversity underwent acute stress induction, eliciting frontolimbic reactivity. High-quality friendships were strongly associated with better mental health. Weak support for friendship stress buffering did not survive multiple comparison correction.
Gesehen am 03.09.2024